Cigarette smoke exposure impairs lipid metabolism by decreasing low-density lipoprotein receptor expression in hepatocytes - Baitao Ma; Yunfei Chen; Xuebin Wang; Rui Zhang; Shuai Niu; Leng Ni; Xiao Di; Qin Han; Changwei Liu (Lipids in Health and Disease, 2020)
Abstract Background Cigarette smoke (CS) exposure impairs serum lipid profiles and the function of vascular endothelial cells, which accelerates the atherosclerosis. However, the precise mechanism and effect on the expression of low-density lipoprotein receptor (LDLR) in the liver by CS exposure is still unclear. Methods In this study, adult male C57BL/6 J mice were divided into three groups, with one group being exposed to CS for 6 weeks. HepG2 cells were treated with CS extract at concentrations of 1, 2.5, 5, and 10%. Results The serum levels of total cholesterol (TC), triglycerides (TGs), and low-density lipoprotein cholesterol (LDL-C) for the CS-exposure group were significantly higher than those in the control group (P < 0.05). Moreover, CS exposure decreased the LDLR expression in the hepatocytes and promoted inflammation in the blood vessel walls. Melatonin was intraperitoneally injected at 10 mg/kg/d for 6 weeks alongside CS exposure, and this significantly decreased the levels of TC, TGs, and LDL-C and decreased the expression of intercellular adhesion molecule-1 and the infiltration of cluster determinant 68-cells. In vitro, CS extract prepared by bubbling CS through phosphate-buffered saline decreased the LDLR expression in HepG2 cells in a time- and concentration-dependent manner, and this effect was prevented by pretreatment with 100 μM melatonin. Conclusions In conclusion, CS exposure impaired lipid metabolism and decreased LDLR expression in hepatocytes, and these effects could be prevented by melatonin supplementation. These findings implied that melatonin has the potential therapeutic applicability in the prevention of lipid metabolic disorder in smokers.